Impact of growing conditions on the gum properties of different genotypes of guar (Cyamopsis tetragonoloba (L.) Taub.) - I. V. Kruchina-Bogdanov; E. V. Miroshnichenko; R. A. Shaukharov; E. N. Kantemirova; M. A. Golovina; K. M. Abdullaev; A. V. Balashov; E. V. Rusinova; P. G. Rusinov; E. K. Potokina (Вавиловский журнал генетики и селекции)
Galactomannan (gum), a water-soluble polysaccharide, is widely used as a gelling agent in liquids, including in the oil and gas industry for hydraulic fracturing. The most effective source of this valuable plant material is seeds of guar (Cyamopsis tetragonoloba (L.) Taub.), a legume crop new for Russia. Although in recent years progress has been made in the selection of guar varieties adapted to the conditions of the Russian Federation, the question of the most appropriate region for the cultivation of this crop remains open. The purpose of the study was to investigate how a region and technology of guar cultivation can affect the main indicators of the final target product: the content and viscosity of guar gum extracted from the seeds of various guar genotypes. To understand this, ecogeographical tests of 13 guar accessions from the VIR collection were conducted at the experimental stations of the Vavilov Institute (VIR), where climatic conditions correspond to the temperature requirements of the crop. To compare the properties of gum extracted from the seeds of various genotypes, a fast-tracked laboratory method was suggested allowing gum extracts to be obtained for assessing their viscosity. The method allows fast screening of the breeding material and selecting guar genotypes with beneficial properties of guar gum which are in demand by the oil industry. Applying the fast laboratory method for assessing the properties of gum in seeds of 13 guar varieties showed that the content and viscosity of gum of the same variety vary greatly depending on growing conditions. The same set of 13 guar accessions was grown in 2018 at the Volgograd, Astrakhan, Dagestan and Kuban VIR experimental stations. As a result, the maximum viscosity values were obtained for the seeds reproduced at the Astrakhan region, where the guar was grown on irrigated lands. On the other hand, the maximum gum content in the seeds of all accessions was recorded when they were grown in the Volgograd region. The results showed that the guar gum extracted from seeds of guar plants grown in the Russian Federation can be used as a gelling agent in the processes of intensification of oil production by the method of hydraulic fracturing. This experience is new to the Russian Federation.